An estimate of seasonality and intensity of infection with gastrointestinal nematodes in sheep and goats . in West Java - Beriajaya .; D.B Copeman (Indonesian Center for Animal Research and Development (ICARD), 1998)
Tracer Inoodle tbin-tail sheep and Kacang goats were used to measure the seasonal changes in gastrointestinal nematodes parasitism i 'und[, .xillapek .Fodd 'ofis in West Java . Each 3 months for 12 months worm-free male sheep (5) and goats (5) about 5 months of age were Jri tgldI o% ef- farmer, and managed as part of their flock for 2 months . Animals were then returned to the laboratory and maintained on